Penerapan Media Kahoot dalam Pembelajaran Bahasa Arab untuk Meningkatkan Motivasi Belajar Siswi Kelas XI-B Madrasah Aliyah Bahrul Ulum Tambakberas Jombang - Muhammad Adib Faizi; Lailatul Mathoriyah; Aufia Aisia (ALSYS, 2026)
Arabic language learning in Madrasah Aliyah continues to face challenges in the form of low active participation among female students and limited variation in learning media, which affect learning motivation. This condition necessitates the use of technology-based media capable of creating interactive, engaging, and enjoyable learning, one of which is Kahoot. This study aims to describe the process of implementing Kahoot in Arabic language learning, identify female students’ responses to its use, and analyze its impact on the learning motivation of Class XI-B female students at Madrasah Aliyah Bahrul Ulum Tambakberas Jombang. The study employed a qualitative approach with a descriptive method. The research subjects were Class XI-B female students at Madrasah Aliyah Bahrul Ulum Tambakberas Jombang. Data were collected through observation, interviews, and documentation and then analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results showed that the implementation of Kahoot created a more active, interactive, and conducive Arabic language learning environment. The female students demonstrated greater enthusiasm and engagement as well as increased motivation to learn. The use of Kahoot also had a positive impact on learning motivation, as indicated by increased attention, participation, self-confidence, and perseverance among the female students during the learning process. This study concludes that Kahoot can be used as an interactive learning medium to increase motivation in learning Arabic. These findings provide practical implications for teachers in developing technology-based learning that is more participatory, engaging, and appropriate to the characteristics of students in Madrasah Aliyah.